Manganese phosphite in Coffee defence against Hemileia vastatrix, the coffee rust fungus: biochemical and molecular analyses. - MONTEIRO, A. C. A. (2016)
Phosphites (Phi) are inorganic salts of phosphorous acid that have been used as resistance elicitors to activate mechanisms underlying plant defence. This study assessed the effectiveness of manganese phosphite (MnPhi) for the management of rust (Hemileia vastatrix) on coffee seedlings. The effect of this compound on the induction of resistance was also measured by the expression of defence-related genes such as POX (peroxidase), CAT (catalase), GLU (b-1.3-glucanase) and PAL (phenylalanine ammonia-lyase) and by the activity of defence enzymes such as ascorbate peroxidase (APX), superoxide dismutase (SOD) and polyphenol oxidase (PPO). Foliar sprayings of MnPhi on coffee seedlings provided 63% control of rust severity. This compound induced defence responses in seedlings with increased transcription of genes POX, CAT, GLU and PAL in non-inoculated plants and increased activity of APX, SOD and PPO enzymes in plants inoculated with H. vastatrix and in non-inoculated plants. It is suggested that MnPhi can induce resistance in coffee seedlings.